Effects of in situ synthesized mullite whisker on mechanical properties of Al2O3–SiC composite by microwave sintering. (6th June 2017) - Dang, Xudan; Wei, Meng; Fan, Bingbing; Guan, Keke; Zhang, Rui; Long, Weimin; Zhang, Hongsong
Abstract: In situ synthesis of mullite whisker was introduced to Al2 O3 –SiC composite by microwave sintering. The effects of sintering parameters (sintering temperature, holding time and SiC particle size) on thermal shock resistance of Al2 O3 –SiC composite were also studied in this paper. Original SiC particles coated with SiO2 by a sol–gel method were reacted with Al2 O3 particles, resulting in the in situ growth of mullite. The phase composition was identified by x-ray diffraction (XRD). The bridging of mullite whisker between Al2 O3 and SiC particles was observed by scanning electron microscopy (SEM) analysis. The thermal shock resistance of samples was investigated through the combination of water quenching and three-point bending methods. The results show that the thermal shock resistance of Al2 O3 –SiC composite with mullite whisker reinforced remarkably, indicating better mechanical properties than the Al2 O3 –SiC composite without mullite whisker. Finally, the optimum process parameters (the sintering temperature of 1500 °C, the holding time of 30 min, and the SiC particle size of 5 µ m) for toughening Al2 O3 –SiC composite by in situ synthesized mullite whisker were obtained.